Antropomorfisme Merek dalam Kajian Filsafat Ilmu - diesyana ajeng pramesti; mugi harsono (Jurnal Manajerial, 2023)
Background – Anthropomorphism refers to the customer's tendency to think of a human characteristic that is in a product or brand and has become a brand positioning strategy that has received attention in marketing research in recent years. Anthropomorphism strategy is needed and becomes an effective alternative strategy in marketing communication, but there is some debate about the success of anthropomorphism strategy in marketing communication. The discrepancy in the findings of the debate makes the anthropomorphism strategy interesting for further research, especially on consumer attitudes. Aim – Anthropomorphism concept is very important in developing a brand for the consumers. Marketing strategies can provide information about the introduction and market’s problems, provide information on alternative solutions, analysis of alternative solutions, and evaluation. The anthropomorphism strategy is used to get closer and communicate the brand to the consumers. This study develops a conceptual framework that describes the philosophy of science about brand anthropomorphism from a marketing perspective. Design/methodology/approach – This study uses secondary data in the form of literature studies and mapping on 78 articles published in Scopus-indexed journals, especially Q1 and Q2 for 47 years from 1975 to 2021. The framework is presented in 3 main aspects that are ontology, epistemology, and axiology. That aspect is discussed in depth in accordance with the development of existing scientific studies. Findings – Brand anthropomorphism is one of the most effective marketing strategies to bring brands closer to their consumers. This study found the antecedents and consequences of brand anthropomorphism, such as brand image congruity, anthropomorphic advertisement, customer intention, willingness to register, etc. These findings, theoretically, it is expected to provide a roadmap for further anthropomorphism research and practice as the input in determining marketing strategies for companies. Research implication – A conceptual model of brand anthropomorphism is presented with an explanation of the influencing factors and the factors that are influenced. This study can help for further research about anthropomorphism. Limitations – This study only refers to Scopus Q1 and Q2 for 47 years from 1975 until 2021.